Electrodeposition of Ni-Mo Defect-Free Alloy from Ammonium-Citrate Electrolyte in Pulse Current Mode. (3rd July 2017) - Karabanov, Sergey M.; Stryuchkova, Yulia M.; Suvorov, Dmitriy V.; Gololobov, Gennadiy P.; Tarabrin, Dmitry Yu.; Rybin, Nikolay B.; Slivkin, Evgeniy V.
ABSTRACT: Electrodeposition in pulse current mode of nickel-molybdenum alloy on a nickel substrate was studied. The range of current density variation from 2 to 9 A/dm 2 was investigated. The range of pulse and pause step lengths is from tens to hundreds of milliseconds. SEM-images of applied coatings surfaces are obtained. The method of energy dispersive spectroscopy determined that the molybdenum content in the coating is 21-24 wt%. It was found that under transient pulse mode of electrolysis, with the pulse step corresponding to hundreds of milliseconds, the most rigid and smooth coatings of the electrolytic nickel-molybdenum alloy are obtained from ammonium-citrate electrolyte. It is shown that the percentage of nickel in the alloy does not depend on the electrolysis mode.